Concordância entre citologia, colposcopia e histopatologia cervical Agreement between cytology, colposcopy and cervical histopathology - Letícia Maria Correia Katz; Alex Sandro Rolland Souza; Simone Oliveira Fittipaldi; Gisele de Melo Santos; Melania Maria Ramos Amorim (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2010)
OBJETIVO: avaliar a concordância da citologia convencional por Papanicolaou repetida no momento da colposcopia com os achados colposcópicos e a histopatologia. MÉTODOS: o estudo foi realizado no Laboratório Central de Saúde Pública do Estado de Pernambuco (LACEN), de janeiro a julho de 2008, em 397 mulheres com exame citopatológico alterado encaminhadas para avaliação colposcópica. No momento da colposcopia, repetiu-se a citologia em meio convencional, pesquisando-se os achados colposcópicos anormais. A nomenclatura citológica utilizada foi a de Bethesda e a histopatológica, da Organização Mundial de Saúde. A citologia no momento da colposcopia e a colposcopia foram comparadas entre si e com o resultado do histopatológico obtido por biópsia dirigida. A concordância entre os métodos foi avaliada pelo coeficiente Kappa (K), além do teste χ2 a um nível de significância de 5%. RESULTADOS: foi encontrada uma concordância fraca entre a citologia realizada no momento da colposcopia e a colposcopia, K=0,33 (IC95%=0,21-0,45) e entre a colposcopia e a histopatologia, K=0,35 (IC95%=0,39-0,51). Para a concordância entre citologia no momento da colposcopia e histopatologia, o Kappa foi de 0,41 (IC95%=0,29-0,530), considerado moderado. CONCLUSÕES: houve melhor concordância entre citologia e histopatologia do que entre colposcopia e citologia ou colposcopia e histopatologia. PURPOSE: to evaluate the agreement between conventional cytology using the Papanicolaou test, repeated at the time of colposcopy, with colposcopic and histopathological findings. METHODS: the study was carried out at the central public health laboratory of the state of Pernambuco between January and July, 2008, involving 397 women referred for colposcopic evaluation following an abnormal cervical smear test. Cytology was repeated at the time of colposcopy using conventional method, with particular attention being paid to the presence of abnormal colposcopic findings. The nomenclature used for cytology was the 2001 Bethesda system terminology, while that used for histology was the World Health Organization 1994 classification. Cytology performed at the time of colposcopy was compared with colposcopy and with histopathology obtained by colposcopy-directed biopsy. The Kappa coefficient was used to evaluate the agreement between methods, as well as the χ2 test, with the level of significance set at 5%. RESULTS: poor agreement was found between cytology performed at the time of colposcopy and colposcopic findings (K=0.33; 95%CI=0.21-0.45) and between colposcopy and histopathology (K=0.35; 95%CI=0.39-0.51). Cytology performed at the time of colposcopy compared with histopathology revealed a Kappa of 0.41 (95%CI=0.29-0.530), which was considered to reflect moderate agreement. CONCLUSIONS: agreement was better between cytology and histopathology than between colposcopy and cytology or between colposcopy and histopathology.